Sodium aescinate-induced hepatotoxicity via ATF4/GSH/GPX4 axis-mediated ferroptosis - Chen Xi; Jie Zhou; Xin Zheng; Xiaoyi Fu; Minjuan Xie (Scientific Reports)
Abstract Sodium aescinate (SA), a natural plant extract with various bioactivities, is widely used to treat oedema and inflammation in clinics. However, adverse events, including liver injury, kidney injury, and phlebitis, have been reported in patients with SA in recent years. In this study, we used BALB/c mice and L02 cells to evaluate the role of ferroptosis in SA-induced liver injury. SA significantly increased AST, ALT, MDA and Fe2+, decreased GSH levels, and induced pathological changes in the liver in vivo. SA also reduced the viability of L02 cells and induced LDH release, intracellular cysteine reduction, GSH depletion, iron accumulation, ROS production, and lipid peroxidation, indicating that SA causes ferroptosis. In addition, SA inhibited transcriptional activity of activating transcription factor 4 (ATF4) and subsequently reduced the expression of the downstream genes xCT (solute carrier family 7a member 11, SLC7A11) and Cystathionine gamma-lyase (CTH) which play vital roles in GSH biosynthesis. Interestingly, the cytotoxic effects of SA were effectively attenuated by ATF4 overexpression, while they were significantly aggravated by ATF4 silencing. These results revealed that SA triggers hepatocyte ferroptosis by inhibiting the activity of ATF4, which causes an oxidative imbalance.